2004
DOI: 10.19173/irrodl.v5i2.186
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Immediacy in Online Learning

Abstract: This article presents the concepts of interaction and immediacy and discusses their theoretical frameworks, implications, and relationship with one another. The authors propose the development of a new conceptual model and recommend additional antecedent research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 22 publications
1
48
0
7
Order By: Relevance
“…There have been research attempts to discover and document better practices for distance teachers to face and to solve the potential problems related to student's learning, fatigue, failing or dissatisfaction (Dennen, Darabi & Smith, 2007). Woods and Baker (2004) add that, when interaction is encouraged, it leads students to positive communication behaviors, like immediacy or psychological closeness with their teacher, social presence and a feeling of community inside the online classroom. Mehrabian (1967b), widely considered the creator of immediacy theory, defines it as the degree in which select communication behaviors improve physical or psychological closeness in interpersonal communication.…”
Section: How Do Teachers Promote Immediacy Through Interaction With Tmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been research attempts to discover and document better practices for distance teachers to face and to solve the potential problems related to student's learning, fatigue, failing or dissatisfaction (Dennen, Darabi & Smith, 2007). Woods and Baker (2004) add that, when interaction is encouraged, it leads students to positive communication behaviors, like immediacy or psychological closeness with their teacher, social presence and a feeling of community inside the online classroom. Mehrabian (1967b), widely considered the creator of immediacy theory, defines it as the degree in which select communication behaviors improve physical or psychological closeness in interpersonal communication.…”
Section: How Do Teachers Promote Immediacy Through Interaction With Tmentioning
confidence: 99%
“…Non-verbal forms refer to psychological closeness through physical communication behaviors, like face expressions, visual contact, posture, proximity, and touch, on the other hand, verbal forms refer to a sense of psychological closeness created through a choice of words. For example, using the word "us" promotes a deeper closeness in relationships and is considered more immediate than "you and me" (Woods & Baker, 2004). In an online modality, this is achieved by the word selection of written messages found in emails and work and discussion forums.…”
Section: How Do Teachers Promote Immediacy Through Interaction With Tmentioning
confidence: 99%
“…These findings are consistent with Arbaugh's (2001) work with MBA students. They provide support to Woods and Baker's (2004) call to create more opportunities for authentic immediacy within online instruction. And, the idea of intentionally using verbal cues to project warmth, sensitivity and sociability is not significantly different from the ideas about immediacy first identified by Albert Mehrabian in the 1960s.…”
Section: Discussionmentioning
confidence: 99%
“…Hutchins (2003) posited that instructor success with immediacy behaviors could advance the current theoretical framework for enhancing instructional effectiveness in distance education. Woods and Baker (2004) suggested that instructors can positively affect the quality of communication in the online environment when they move from mere interaction to authentic immediacy and interpersonal closeness.…”
Section: Immediacy In Higher Educationmentioning
confidence: 99%
“…Following Bandura's supposition, high levels of interaction which promote social engagement can have positive effects on the learning experience. Woods and Baker [6] suggested that failing to consider the relational dynamics in the online setting may produce greater social isolation among distance learners, reduced levels of student satisfaction, poor levels of student satisfaction, poor academic performance, and increased attrition.…”
Section: Interactivity In Learningmentioning
confidence: 99%